Study regarding game technique and long-lasting training in handball - Ghervan, P. (Annals of the University Dunarea de Jos Galati, Fascicle XV: Physical Education and Sport Management, 2016)
Sports excellence is achieved through native outstanding qualities, exploited in a proper training regime, along the entire sports career. Training quality depends to a great extent to the allocated time for this purpose to training process, concretized in number of executions at high efforts parameters. The means that determine a maximal commitment of the athlete are those that involve emotional involvement in order to achieve an immediate result. Long-term, this way of approach differentiates the athletes who train in similar conditions of material base, time resources and so on. Analyzing sports career of some players that are internationally recognized, I reached the conclusion that technical excellence and of course the sports value are based on the number of efficient repetitions - repetitions with maximum request, through athlete`s emotional involvement.